2015
DOI: 10.1002/smll.201402591
|View full text |Cite
|
Sign up to set email alerts
|

Microlandscaping of Au Nanoparticles on Few-Layer MoS2Films for Chemical Sensing

Abstract: Surface modification or decoration of ultrathin MoS2 films with chemical moieties is appealing since nanointerfacing can functionalize MoS2 films with bonus potentials. In this work, a facile and effective method for microlandscaping of Au nanoparticles (NPs) on few-layer MoS2 films is developed. This approach first employs a focused laser beam to premodify the MoS2 films to achieve active surface domains with unbound sulfur. When the activated surface is subsequently immersed in AuCl3 solution, Au NPs are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 51 publications
2
89
0
Order By: Relevance
“…3(c) and (d) displays a typical TEM image of as-prepared product, It can be seen that the Au distribute to MoO 3 sheets averagely, the sizes of the Au nanoparticles are within the range of 10-15 nm, Moreover, the interlayer distance is 0.46 nm, which is consistent with the theoretical spacing for (111) planes. Combined with XRD, SEM, TEM and XPS analysis of the samples, it can be deduced the successful synthesis of Au@MoO 3 nanocomposites [31][32][33]. To find the optimum detection temperature, we investigated the sensor responses to 200 ppm ethanol at the operating temperature from 200 • C to 360 • C shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3(c) and (d) displays a typical TEM image of as-prepared product, It can be seen that the Au distribute to MoO 3 sheets averagely, the sizes of the Au nanoparticles are within the range of 10-15 nm, Moreover, the interlayer distance is 0.46 nm, which is consistent with the theoretical spacing for (111) planes. Combined with XRD, SEM, TEM and XPS analysis of the samples, it can be deduced the successful synthesis of Au@MoO 3 nanocomposites [31][32][33]. To find the optimum detection temperature, we investigated the sensor responses to 200 ppm ethanol at the operating temperature from 200 • C to 360 • C shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, we show that liquid phase exfoliated MoS 2 nanoflakes and LBL assembly of these materials offer an efficient LDI-MS platform for the analysis of small molecule, providing simple preparation, high LDI-MS efficiency and compatibility for chip-based analysis. Furthermore, we believe that the present [MoS 2 nanoflake] n films can be utilized as a support to synthesize a multifunctional nanohybrid structures with dielectric 47 and metallic nanostructures 48 for multi-modal analysis with surface plasmon resonance (SPR) and surface enhanced Raman scattering (SERS), respectively. From this point of view, the surface chemistry with thiol derivatives and high LDI-MS efficiency will play an important role for the development of a multi-modal analysis platform combining LDI-MS with other sensing technique such as SPR and SERS.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [121] have shown that use of a similar Au@MoS 2 nanocomposite as the substrate leads to a considerable enhancement of the Raman peaks for organic dyes, namely, rhodamine 6G (amplification coefficient 307.9), methylene blue (218.5), and rhodamine 101 (1843.5). We should note that the intensity of the analyte signals varies depending on the size of the gold NP and their density on the semiconductor surface.…”
Section: Sensorsmentioning
confidence: 98%
“…Controlled deposition of structural defects on TMDC sheets proposed by Lu et al [121] is interesting and holds promise for possible practical application. These authors showed that laser irradiation (including procedures with various stencils) leads to defect-rich areas on the surface of MoS 2 sheets.…”
Section: Reduction Of Metal Salts By Oxidation Of Tmdcmentioning
confidence: 99%